Analysis the development of growth centers and hinterland areas in Bangka Regency, Indonesia - Sella Agustina; Devi Valeriani; Anggraeni Yunita (Goodwood Publishing, 2021)
Purpose: This study aims to determine and analyze the development of growth centers and hinterland areas in Bangka Regency, Indonesia. Research Methodology: The analytical methods used are scalogram analysis, centrality index, gravity analysis, and GIS (Geographic Information System) methods. The type of data is quantitative data. The data source is secondarily obtained from BPS of Bangka Regency. Results: The results of the scalogram analysis and centrality index showed that Sungailiat District had the first order as the center of growth. The other seven districts, namely Belinyu, Merawang, Mendo Barat, Pemali, Riau Silip, Puding Besar, and Bakam are hinterland areas. Sungailiat District as the growth center has the strongest interaction value with the hinterland area, namely Pemali District, and the weakest interaction value with Bakam District. Limitations: This research uses the descriptive quantitative approach in its calculations using simple mathematical calculations. Further research is needed to find out how much influence it has on the region. Contributions: This study is to provide alternative inputs to the government of the Bangka Regency in formulating policy planning and decision-making regarding growth centers and hinterland areas.